Prediction for the Total MRI Burden of Cerebral Small Vessel Disease With Retinal Microvascular Abnormalities in Ischemic Stroke/TIA Patients - Shu, Liming; Liang, Jiahui; Xun, Weiquan; Yang, Hong; Lu, Tao (Frontiers in Neurology, 2020)
Background and Purpose: The association of retinal microvascular abnormalities with the total cerebral small vessel disease (cSVD) burden found on brain MRI has not been determined. In the present study, we examined whether the retinopathy score could predict the total cSVD burden in ischemic stroke/transient ischemic attack (TIA) patients. A simple practical diagnostic tool may help identify candidates for MRI screening. Methods: We consecutively collected clinical data including retinal photography and cerebral MRI of ischemic stroke/TIA patients from August 2016 to August 2017 at our stroke center. The retinopathy score was assessed by the Keith-Wagener-Barker grading system for analyzing retinal microvascular abnormalities. To evaluate the total cSVD burden, the total cSVD score was assessed by awarding one point for the presence of each marker of cSVD on MRI. The clinical characteristics and retinopathy score were analyzed across patients for each total cSVD score. The association between the retinopathy score and the total cSVD score was analyzed. Results: Among the 263 enrolled patients, the frequency of hypertension in patients with a total cSVD score of 2, 3, or 4 was higher than that in patients with a score of 0 (69.5, 71.7, and 89.2% vs. 45.2% respectively, all P < 0.05). The retinopathy score was related to the total cSVD score (r = 0.687, P < 0.001). Adjusted multivariate ordinal regression showed that the retinopathy score was independently correlated with the total cSVD score (odds ratio [OR], 4.18; 95% confidence interval [CI], 3.07–5.70) after adjustment for age, history of hypertension, previous stroke/TIA and current smoking. The c statistics were 0.30 (95% CI, 0.24–0.37; P < 0.05), 0.46 (95% CI, 0.39–0.53; P = 0.303), 0.79 (95% CI, 0.72–0.86; P < 0.001), and 0.81 (95% CI, 0.74–0.88; P < 0.001) for predicting the total cSVD score of 1, 2, 3, and 4 respectively. Conclusions: These results suggest that retinal microvascular abnormalities have predictive value for severe total cSVD burden in ischemic stroke/TIA patients.